Coating composition containing an alkali salt of graphene oxide and coating layer produced from said coating composition
Patent Information
- Application Number
- JP2023524890
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-22
- Filing Date
- 2021-10-13
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2041-10-13
AI Technical Summary
【0019】 先行技術に照らして、リチウムイオン及び/又はカリウムイオンを含有するグラフェンオキシド(以下、グラフェンオキシド塩と呼ぶ)を使用することによって、本発明の基礎となる目的を達成できることは、当業者にとって驚くべきことであり、予測不可能であった。前記グラフェンオキシド塩を、少なくとも1つのバインダー(すなわち有機コーティング組成物)及び/又は少なくとも1つのシラン化合物を含む液体コーティング組成物(以下、化成コーティングとも呼ぶ)に組み込むと、グラフェンオキシドを含むコーティング組成物、又はバインダー及び/又はシラン化合物のみを含むコーティング組成物と比較して、防食性が著しく改善される結果となる。グラフェンオキシド塩が存在するにもかかわらず、本発明のコーティング組成物は傑出した貯蔵安定性と高いポットライフを有し、そして一般的に使用される適用具、例えば空気圧又は静電噴霧ガン、ローラー塗布、又はコイルコーティングによって適用することができる。さらに、本発明のコーティング組成物は、基材に対して優れた付着性を示すので、基材に直接適用することができ、化成コーティング層をあらかじめ適用する必要がない。さらに、本発明のコーティング組成物は、さらなる下層の及び/又は上層のコーティング層に対する優れた付着性も有するので、多層コーティング系を調製する方法におけるプライマー、プライマー-サーフェーサー又はフィラーとして容易に好適なものとなる。さらに、本発明のコーティング組成物から得られたコーティング層の可撓性は、グラフェンオキシド塩の添加によって否定的に損なわれることがないので、被覆された基材の屈曲時に、本発明のコーティング組成物が生成するコーティング層の亀裂形成を低減する。
Smart Images

Figure 0007651692000001 
Figure 0007651692000002 
Figure 0007651692000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a coating composition comprising at least one graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof, at least one binder B and / or silane compound SC and at least one solvent S1. Furthermore, the present invention relates to a method for producing the coating composition of the present invention, a method for producing at least one coating layer on a substrate using the coating composition of the present invention, and a coating layer or multi-layer coating obtained by said method. Finally, the present invention relates to the use of graphene oxide containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof in a coating composition in order to improve the corrosion protection properties of said coating composition. [Background technology]
[0002] Corrosion of metallic materials is a problem that has not been satisfactorily solved to date. Corrosion is the electrochemical reaction of metallic materials with their atmospheric surroundings, more particularly with oxygen and water, which leads to significant changes and damage to the material. As a result of said damage, the functionality of the metallic components is impaired and repair or replacement is required. The economic implications of corrosion, and therefore protection against corrosion, are therefore of great importance.
[0003] For these reasons, corrosion control is of great importance in virtually all sectors of the metals industry (e.g. mechanical engineering and equipment, automotive industry (vehicle construction), aviation and aerospace industry, shipbuilding industry, electrical industry, precision machinery industry, construction industry and household appliances / "white goods"), but especially in the automotive and aviation sectors. Especially in the latter sectors, metal substrates are used very extensively as components exposed to atmospheric conditions, sometimes even extreme atmospheric conditions.
[0004] In the vehicle finishing and aeronautical industries, metal substrates are generally subjected to expensive multi-layer coating procedures, which are necessary to be able to meet the demands of automobile manufacturing and the aeronautical industry, which include, for example, effective corrosion control.
[0005] Generally, a conversion coating is first applied to the metal substrate, which protects the substrate from corrosion and improves adhesion with the overlying coating layer. Examples include phosphating steel substrates or chromating aluminum substrates or aluminum alloys, such as 2000-7000 series aluminum alloys, such as AA2024, AA5083, AA6111, AA6014, AA6061 and AA7075. The latter is mainly applied in the aviation industry due to its very good processing properties, its low density and at the same time its resistance to physical stress. But at the same time, this material is prone to harmful filiform corrosion, which often combines with high atmospheric humidity to cause physical damage to the substrate coating, after which the corrosion propagates in a filiform manner under the substrate coating and causes filiform corrosion damage to the metal substrate. Therefore, effective corrosion control is important.
[0006] Following the pretreatment and the production of a suitable conversion coating, a primer coat is usually applied to provide additional protection against corrosion. This primer coat is based on an organic polymer matrix and may further contain anti-corrosive pigments, as described below. In the context of the automotive industry, this primer coat generally constitutes an electrocoat coating, more specifically a cathodic electrocoat (also known as an ED coat). In the aircraft industry, special epoxy resin-based primers are usually used. In the automotive finishing sector, a surfacer coating is then generally applied to correct any irregularities still present on the surface of the coated substrate and to protect the cathodic electrocoat from damage caused by stone chipping. In the last step, a topcoat is applied, which consists of two separately applied coatings, namely a base coat and a clear coat.
[0007] One form of corrosion protection that is still in use for metal substrates is chromate compounds. Chromate compounds are included in conversion coatings, for example, as part of the surface pretreatment (also called chromate treatment) of metal substrates. Similarly, chromate compounds in the form of chromate salts (e.g., barium chromate, zinc chromate, strontium chromate) are frequently used as anticorrosive pigments in anticorrosive coating compositions based on organic polymer resins, preferably primers, primer-surfacers or fillers.
[0008] The corrosion protection effect of chromate compounds in conversion coatings is achieved by the simultaneous proportional reduction of the chromate compounds to trivalent chromium with etching of the metal surface (e.g. aluminum), whereas low-solubility passivating coatings contain aluminum(III) / chromium(III) / chromium(VI) oxide hydrates to achieve the corrosion protection effect.
[0009] However, a related problem is the high toxicity and carcinogenic effects of chromate compounds. Therefore, avoiding chromate compounds in the automotive, appliance and aviation industries while maintaining adequate protection against corrosion is a long-standing demand in the corresponding sectors of industry.
[0010] As an example of one possible approach to avoid chromate compounds while still maintaining adequate protection from corrosion, various transition metal oxoanions (and / or their salts), such as MoO4 2- , MnO4 - and VO3 - The use of lanthanide cations or different organic species, such as benzotriazole, ethylenediaminetetraacetic acid (EDTA), quinoline derivatives or phosphate derivatives, is also known. The mechanism of action is complex and is not yet fully understood. It ranges from the formation of a passive oxide / hydroxide coating on the corroding metal surface to the complexation of certain metal cations (e.g. Cu(II)), which can result in the inhibition of certain corrosion forms (e.g. filiform corrosion of aluminum-copper alloys).
[0011] A further approach is the use of so-called nanocontainer materials and / or layered structure materials, such as organic cyclodextrins or inorganic materials, such as zeolites, alumina nanotubes and smectites. Hydrotalcite components and layered double hydroxide materials are also used. The latter are usually referred to by the abbreviation "LDH" in the general technical literature. They are often described in the literature with the idealized general formula [M2 2+ (1-x) M3 3+ x(OH)2] x+ [A y - (x / y) nH2O] or a similar empirical formula. In these formulas, M2 represents a divalent metal cation, M3 a trivalent metal cation, and A an anion of valence x. In the case of naturally occurring LDHs, these are generally inorganic anions, such as carbonate, chloride, nitrate, hydroxide and / or bromide. In synthetic LDHs, various further organic and inorganic anions may also be present. In the above general formula, water of crystallization is also taken into account. In the case of hydrotalcite, the divalent cation is Mg 2+ and the trivalent cation is Al 3+ and the anion is carbonate, although the latter may be replaced at least in part by hydroxide ions or other organic and inorganic anions. Hydrotalcites and LDHs have a layered structure similar to that of brucite (Mg(OH)2), in which a negatively charged layer of intercalated anions, generally containing water of crystallization, is present between each pair of positively charged metal hydroxide layers, due to the presence of a positively charged trivalent metal cation. In the above formula, the LDH layer structure is described by the brackets arranged accordingly. Various agents, such as the rust inhibitors mentioned above, can be intercalated between two adjacent metal hydroxide layers by non-covalent, ionic and / or polar interactions.
[0012] The nanocontainer materials and / or LDH materials described above can be directly incorporated into corresponding coating materials based on polymer binders, such as conversion coating materials and / or primer materials. Attempts are also being made to completely replace conversion coatings, in which case a corresponding primer is applied directly to the metal. In this way, the complexity of the coating procedure is reduced, and therefore more cost-effective.
[0013] Recent research has focused on incorporating graphene, a crystalline graphite sheet with a thickness of one atom or a few layers, or graphene oxide into corrosion protection coatings due to its excellent chemical resistance, mechanical strength, and impermeability to gases and corrosive ions. Compared with graphene, graphene oxide has more oxygen-containing organic functional groups on its surface, which increases its compatibility and interface structure with some organic resins, such as epoxy resins. However, the incorporation of graphene oxide into organic coatings has not been proven to fully meet the requirements of corrosion protection in the automotive, aviation, home appliance and construction industries.
[0014] Thus, what would be advantageous would be a coating composition that has excellent corrosion protection without the use of toxic compounds, such as chromium and other heavy metal compounds, as well as fluoro- and phosphate-containing compounds. The coating composition should have excellent storage stability and be applicable to commonly used application equipment. Furthermore, the composition should have excellent adhesion to the metal substrate and to any underlying and / or overlying coating layers, so that it can be applied directly onto the metal without a prior conversion layer, as well as to further coating layers to produce multi-layer coatings. Summary of the Invention [Problem to be solved by the invention]
[0015] It was therefore an object of the present invention to provide a coating composition with excellent corrosion protection without the use of toxic compounds, such as chromium and other heavy metal compounds, fluoro compounds and phosphate-containing compounds. The coating composition must have excellent storage stability and be applicable to commonly used application equipment. Furthermore, the coating composition should have a high pot life and excellent adhesion to the substrate as well as to any underlying and / or overlying coating layers. The coating composition must therefore be able to be overcoated without any problems with commonly used coating compositions, such as filler, base coat and / or top coat compositions. Furthermore, the coating composition must result in a coating layer with sufficient flexibility so that the coated substrate can be deformed without cracking the coating layer obtained from the coating composition of the present invention.
[0016] The above objectives are achieved by the subject matter as claimed and by preferred embodiments of that subject matter as set forth in the following description. [Means for solving the problem]
[0017] The first subject of the invention is therefore a) at least one graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof; b) at least one binder B and / or at least one silane compound SC, and c) at least one solvent S1 A coating composition comprising:
[0018] The above specified coating composition is hereinafter also referred to as the inventive coating composition and is therefore the subject of the present invention. Preferred embodiments of the inventive coating composition are evident from the following description and also from the dependent claims.
[0019] In light of the prior art, it was surprising and unpredictable for a person skilled in the art that the object underlying the present invention could be achieved by using graphene oxide containing lithium and / or potassium ions (hereinafter referred to as graphene oxide salt). The incorporation of said graphene oxide salt into a liquid coating composition (hereinafter also referred to as conversion coating) comprising at least one binder (i.e. an organic coating composition) and / or at least one silane compound results in a significantly improved corrosion protection compared to a coating composition comprising graphene oxide or a coating composition comprising only a binder and / or a silane compound. Despite the presence of graphene oxide salt, the coating composition of the present invention has outstanding storage stability and a high pot life and can be applied by commonly used applicators, such as pneumatic or electrostatic spray guns, roller application, or coil coating. Furthermore, the coating composition of the present invention exhibits excellent adhesion to the substrate and can therefore be applied directly to the substrate, without the need for a prior application of a conversion coating layer. Furthermore, the coating composition of the present invention also has excellent adhesion to further underlying and / or overlying coating layers, which makes it easily suitable as a primer, primer-surfacer or filler in the process of preparing a multi-layer coating system. Moreover, the flexibility of the coating layer obtained from the coating composition of the present invention is not negatively impaired by the addition of the graphene oxide salt, which reduces the crack formation of the coating layer produced by the coating composition of the present invention upon bending of the coated substrate.
[0020] A further subject of the present invention is a process for producing a method for the production of a compound comprising the steps of: (a) preparing a dispersion D of at least one graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof in at least one solvent S2, (b) adding the dispersion D prepared in step (a) to a mixture containing at least one binder B and / or at least one silane compound SC and at least one solvent S1; A method for producing the coating composition of the present invention comprising:
[0021] Another subject of the present invention is a method for producing a process comprising the steps of: (i) applying a coating composition of the present invention or a coating composition prepared by the method of the present invention directly onto a substrate (S); (ii) forming a film from the coating composition applied in step (i) by curing the coating composition; and (iii) optionally applying at least one further coating composition to the coating layer formed in step (ii) and curing said coating composition. The method for forming at least one coating layer on a substrate (S) comprises:
[0022] Yet another subject of the invention is a coating layer or a multilayer coating (MC) produced by the method according to the invention.
[0023] A final subject of the present invention is the use in a coating composition of at least one graphene oxide containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof to improve the corrosion protection properties of said coating composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] Detailed Description The measurement methods used in the context of the present invention to determine certain characteristic variables can be found in the Examples section. These measurement methods are used to determine the respective characteristic variables, unless expressly indicated otherwise. In the context of the present invention, when reference is made to an official standard without any indication of the valid official period, the reference is implicitly to the version of the standard valid at the filing date, or to the latest version if there is no valid version at that time.
[0025] The term "graphene oxide" generally refers to a compound having the following general structure: [ka] This refers to oxidized graphene having the following structure:
[0026] Thus, graphene oxide comprising at least one monovalent metal ion refers to graphene oxide in which at least one carboxylic acid group has been converted to at least one carboxylate group having a counterion of at least one monovalent metal.
[0027] Any film thickness reported in the context of the present invention should be understood as a dry film thickness. It is therefore in each case the thickness of the cured film. Thus, when a coating material is reported to be applied at a specific film thickness, this means that the coating material is applied to the stated film thickness after curing.
[0028] The coating composition of the present invention: The coating composition of the present invention comprises at least one graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof, at least one binder B and / or at least one silane compound SC and at least one solvent S1. The coating composition of the present invention is therefore preferably a coating composition that is liquid at 23° C.
[0029] Graphene oxide containing at least one monovalent lithium ion and / or potassium ion: For the preparation of graphene and graphene oxide, various methods have been described in the state of the art. They can be basically divided into two categories: "top-down" and "bottom-up" approaches. In the first technique, graphite as starting material is mechanically, electrochemically or thermally exfoliated and oxidized to obtain graphene oxide. The most frequently used "top-down" techniques are the Hummers and modified Hummers methods, which use strong oxidizing agents such as sulfuric acid, sodium nitrate or potassium permanganate in combination with a catalyst. A further "top-down" technique is the electrochemical approach, where the exfoliation is achieved by applying an electric current that causes the intercalation of different ionic species of the electrolyte used into the graphite layers.
[0030] The graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof contained in the coating composition of the present invention is preferably obtained by adding a solution of the respective metal salt to graphene oxide, followed by ultrasonic treatment, filtration and drying of the residue. The graphene oxide is preferably prepared by a two-step electrochemical exfoliation method in which graphene rods are placed in a NaOH solution and exfoliated by applying an anionic current using a two-electrode system. In the subsequent step, anionic electrolysis is performed in an aqueous sulfuric acid solution to obtain graphene oxide.
[0031] The monovalent metal ion is selected from the group consisting of lithium, potassium, and mixtures thereof. Particularly preferably, the monovalent metal ion is lithium. The use of graphene oxide containing lithium ions (i.e., graphene oxide functionalized with lithium ions) provides excellent corrosion protection for organic or conversion coating compositions.
[0032] Surprisingly, excellent corrosion protection properties of organic and conversion coating compositions comprising graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof, preferably graphene oxide containing lithium ions, are already achieved when small amounts of said graphene oxide (GO-M) are incorporated into the composition. The coating compositions preferably contain at least one graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof, preferably graphene oxide containing at least one lithium ion, in a total amount of 0.1 ppm to 5 wt.-%, more preferably 0.5 to 2 wt.-%, even more preferably 0.1 ppm to 1 wt.-%, even more preferably 0.1 ppm to 500 ppm, even more preferably 0.3 to 50 ppm, very preferably 0.35 to 1 ppm, in each case relative to the total weight of the coating composition.
[0033] Binder B, Silane Compound SC: The aqueous coating composition of the present invention comprises as a second essential component (b) at least one binder B and / or at least one silane compound SC.
[0034] Binder B: A "binder" in the context of the present invention and according to DIN EN ISO4618:2007-03 is a non-volatile component of the coating composition that does not contain pigments and fillers. However, this expression is used below mainly in connection with certain physically hardening polymers, which may optionally be thermosetting, such as polyurethanes, polyesters, polyacrylates and / or copolymers of the mentioned polymers. The term "binder" in the sense of the present invention therefore does not include hardeners or crosslinkers used to crosslink the binder to effect film formation. A copolymer in the context of the present invention refers to polymer particles formed from different polymers. This explicitly includes both polymers that are covalently bonded to each other and different polymers that are bonded to each other by adhesion. Combinations of the two types of bonds are also included in this definition.
[0035] In the context of the present invention, the term "physical curing" refers to film formation by evaporation of solvent from a polymer solution or dispersion. Typically, no crosslinking agent is required for this curing.
[0036] In the context of the present invention, the term "thermal curing" refers to the thermally initiated crosslinking of a coating film using either a self-crosslinking binder or a separate crosslinking agent in combination with a binder (external crosslinking). The crosslinking agent contains reactive functional groups that are complementary to the reactive functional groups present in the binder, so that upon reaction of the binder and the crosslinking agent, a macroscopically crosslinked coating film is formed.
[0037] The binder components present in the coating compositions of the present invention always exhibit at least some physical cure, and thus, when a coating composition is said to contain a binder component that is thermosetting, this does not, of course, exclude cure, including some physical cure.
[0038] The selection and combination of suitable binders B is made according to the desired and / or required properties of the coating system to be produced. Another criterion for the selection is the desired and / or required curing conditions, more particularly the curing temperature. The skilled person knows how to make such a selection and can adapt accordingly. If the coating composition of the present invention is an aqueous coating composition, ionically or nonionically stabilized polymers are used as binders B. Anionically stabilized polymers are known to be polymers modified with anionic groups and / or functional groups, which can be converted to anions by neutralizing agents (e.g. carboxylate and / or carboxylic acid groups), to facilitate their dissolution or dispersion in water. Nonionically stabilized polymers are polymers modified with polyoxyalkylene groups to increase their water solubility or dispersibility in water. Suitable binders B are selected from the group consisting of (i) poly(meth)acrylates, more particularly hydroxy- and / or carboxylate- and / or amine-functional poly(meth)acrylates, (ii) polyurethanes, more particularly hydroxy- and / or carboxylate- and / or amine-functional polyurethanes, (iii) linear or branched polyesters or polyamide-modified polyesters, more particularly linear or branched polyester polyols, (iv) polyethers, more particularly polyether polyols, (v) polyepoxides, (vi) phenoxy resins, (vii) copolymers of the mentioned polymers and (vi) mixtures thereof, preferably polyepoxides, linear or branched polyester and / or polyester polyurethane copolymers.
[0039] Suitable hydroxyl-functional polymers and / or resins have a hydroxyl number of 30-400 mg KOH / g solids, more preferably 100-300 KOH / g solids, determined according to DIN 53240-2:2007-11. In the case of pure poly(meth)acrylates, the OH number can also be determined with sufficient accuracy by calculation based on the OH-functional monomers used. The acid number can be 0-30 mg KOH / g solids, determined according to DIN EN ISO 2114:2006-11.
[0040] The glass transition temperature of the hydroxyl functional polymers and / or resins, determined by DSC measurement in accordance with DIN EN ISO11357-2:2014-07, is preferably between -150°C and 100°C, more preferably between -120°C and 80°C.
[0041] Suitable polyester polyols are described, for example, in EP-A-0994117 and EP-A-1273640. In one or more embodiments, polyurethane polyols are prepared by reaction of polyester polyol prepolymers with suitable di- or polyisocyanates, as described, for example, in EP-A-1273640. Suitable polysiloxane polyols are described, for example, in WO-A-01 / 09260, where the polysiloxane polyols described therein are preferably used in combination with other polyols, more particularly those having high glass transition temperatures.
[0042] Suitable poly(meth)acrylate polyols have a weight average molecular weight M w between 1,000 and 20,000 g / mol, more particularly between 1,500 and 10,000 g / mol, determined in each case by gel permeation chromatography (GPC) against polystyrene standards.
[0043] The poly(meth)acrylate polyol preferably contains at least one hydroxyl functional monomer, and optionally further monomers, such as alkyl(meth)acrylates and / or vinyl aromatic monomers and / or acid functional unsaturated monomers.Suitable hydroxy functional monomers are hydroxyalkyl(meth)acrylates, such as more particularly 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 3-hydroxypropyl(meth)acrylate, 3-hydroxybutyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate and mixtures thereof. Suitable alkyl (meth)acrylates are, for example, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, hexyl (meth)acrylate, ethylhexyl (meth)acrylate, 3,3,5-trimethylhexyl (meth)acrylate, stearyl (meth)acrylate or lauryl (meth)acrylate, cycloalkyl (meth)acrylates such as cyclopentyl (meth)acrylate, isobornyl (meth)acrylate or cyclohexyl (meth)acrylate and mixtures thereof.Suitable vinyl aromatic monomers are, for example, vinyl toluene, alpha-methylstyrene or in particular styrene, amides or nitriles, vinyl esters or vinyl ethers of acrylic acid or methacrylic acid.Suitable acid-functional unsaturated monomers are, for example, acrylic acid and / or methacrylic acid.
[0044] According to a first particularly preferred embodiment, the at least one binder B is selected from polyepoxides. Polyepoxides in the sense of the present invention are polymers which contain, on average, at least one epoxy group per molecule. The polyepoxides which can be used according to the invention are preferably selected from the group consisting of glycidyl ethers, such as bisphenol-A-diglycidyl ether, bisphenol-F-diglycidyl ether, epoxide-novalac, epoxide-o-cresol-novolac, 1,3-propane-, 1,4-butane- or 1,6-hexane-diglycidyl ether and polyalkylene oxide glycidyl ethers, glycidyl esters, such as diglycidyl hexahydrophthalate, glycidyl amines, such as diglycidyl aniline or tetraglycidyl methylene dianiline, cycloaliphatic epoxides, such as 3,4-epoxycyclohexyl epoxyethane or 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, and glycidyl isocyanurates, such as trisglycidyl isocyanurate. These compounds contain hydroxyl groups along the chain and epoxide groups at the ends. The ability of an epoxy resin to crosslink by epoxide groups and by hydroxyl groups varies with its chain length. The ability to crosslink by epoxide groups decreases with increasing chain length and molar mass, whereas the ability to crosslink by hydroxyl groups increases with increasing chain length. In the context of the present invention, it is finally possible to use any epoxy resin known per se to the person skilled in the art, for example the commercially available epoxy resins specified below, which are obtained as solutions or dispersions in organic solvents or water. Particularly preferably, the at least one binder B has an epoxy equivalent weight (EEW) of 100 to 400 g / eq, preferably 150 to 350 g / eq, very preferably 200 to 300 g / eq, determined in accordance with DIN EN ISO 3001:1999-11.
[0045] If the at least one binder B is selected from a polyepoxide, it is particularly preferred that the at least one binder B is selected from a mixture of two different polyepoxides, where the first polyepoxide B1 has a dynamic viscosity (determined according to ASTM D445-06) of 0.5 to 2 Pa*s and the second polyepoxide B2 has a dynamic viscosity (determined according to DIN EN ISO 3219:1994-10 at a shear rate of 500 1 / s and 23°C) of 800 to 1400 mPa*s. The use of said mixture of polyepoxides in combination with graphene oxide containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof (GO-M), preferably graphene oxide functionalized with at least one lithium ion, results in excellent corrosion protection without adversely affecting high storage stability, pot life, adhesion to the substrate and interlayer adhesion.
[0046] Epoxy resins of this kind are available, for example, in the form of solutions or dispersions in organic solvents or in water, from the company Cytec under the trade name Beckopox, or from the company Momentive under the trade name Epikote.
[0047] According to a second particularly preferred embodiment, the at least one binder B is selected from linear and / or branched polyesters, preferably linear polyesters. The use of a combination of linear and branched polyesters makes it possible to adjust the flexibility of the coating composition by varying the ratio between said polyesters, thus making it possible to adapt the coating composition of the invention to the specific intended application of the coated substrate.
[0048] In this respect, the at least one linear polyester preferably has a weight average molecular weight of 2,000 to 30,000 g / mol, more preferably 2,500 to 25,000 g / mol, even more preferably 3,000 to 20,000 g / mol and very preferably 3,000 to 17,000 g / mol, determined in accordance with DIN EN ISO 16014-5.
[0049] If the binder B is chosen from polyesters, it is preferred if the coating composition comprises at least two different linear polyesters P1 and P2, the polyester P1 having a weight average molecular weight of 2,000 to 9,000 g / mol, preferably 3,000 to 6,000 g / mol, and the linear polyester P2 having a weight average molecular weight of 10,000 to 20,000 g / mol, preferably 14,000 to 16,000 g / mol, the weight average molecular weights being determined in each case in accordance with DIN EN ISO 16014-5.
[0050] A suitable weight ratio of the at least one linear polyester P1 to the at least one polyester P2 is, for example, from 2:1 to 1:2, preferably from 2:1 to 1:1.
[0051] The at least one linear polyester preferably has a hydroxyl number of 20 to 100 mg KOH / g, preferably 30 to 80 mg KOH / g, more preferably 40 to 70 mg KOH / g, determined in accordance with DIN 53240-3:2016-03.
[0052] Suitable linear polyesters have a glass transition temperature T g which were determined by differential scanning calorimetry in accordance with DIN EN ISO11357-2:2014.
[0053] Such linear polyesters are commercially available, for example, under the trade names Dynapol L205 (Degussa) and Uralac SH970 (DSM).
[0054] Advantageously, the coating composition comprises at least one binder B, preferably at least one polyepoxide or at least one linear polyester, in a total amount of 1 to 40% by weight solids, preferably 5 to 30% by weight solids and very preferably 15 to 20% by weight solids, in each case based on the total amount of the coating composition. The use of the aforementioned amounts of binder ensures sufficient and stable film formation on the substrate.
[0055] Silane Compound SC: When the coating composition of the present invention is a conversion coating, it preferably contains at least one silane compound SC.
[0056] Said silane compound SC is preferably chosen from silane compounds comprising at least one primary amino group and at least one hydrolyzable alkoxy group.
[0057] Particularly preferred silane compounds SC are those of the general formula (I) NH2-R 1 -YR 2 -Si(R a ) 3-x (R b ) x (I) (In the formula, R 1 , R 2 are, independently of each other, an alkylene group containing 1 to 10 carbon atoms, R a is an alkoxy group containing 1 to 4 carbon atoms, R b is an alkyl group containing 1 to 4 carbon atoms or an alkoxy group containing 1 to 4 carbon atoms, Y is oxygen, sulfur or NR 3 is a group, R 3 is hydrogen or an alkyl group containing 1 to 4 carbon atoms, and (x is 0 to 1) has.
[0058] Preferably, R1 is a C2 alkylene group, and / or R 2 is a C3 alkylene group.
[0059] Furthermore, R in the general formula (I) a is an alkoxy group containing 1 carbon atom and x is 0.
[0060] In the general formula (I), Y is an NH group.
[0061] A particularly preferred silane compound SC is (3-(2-aminoethylamino)propyltrimethoxysilane, i.e. R 1 is a C2 alkylene group, R 2 is a C3 alkylene group, R a is an alkoxy group containing 1 carbon atom, x is 0, and Y is an NH group.
[0062] The coating composition preferably comprises at least one silane compound SC, preferably a silane compound of general formula (I), in a total amount of 2-20% by volume, more preferably 5-15% by volume, in each case relative to the total volume of the coating composition. The use of said amounts of silane compound SC in combination with graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof, results in a coating composition that provides excellent adhesion as well as corrosion protection to substrates treated with the coating composition.
[0063] Solvent S1: The aqueous coating composition of the present invention comprises, as a third essential component (c), at least one solvent S1.
[0064] Suitable solvents S1 are selected from the group consisting of water, aliphatic and / or aromatic hydrocarbons, ketones, esters, or mixtures thereof. If solvent S1 is selected from water, the coating composition is an aqueous coating composition. If the coating composition of the present invention is a solvent-based coating composition, it comprises at least one organic solvent S1. Organic solvents are used that do not inhibit the crosslinking of the coating composition of the present invention and / or do not chemically react with other components of the coating composition of the present invention. Thus, a person skilled in the art can easily select a suitable solvent based on its known solubility and its reactivity. Particularly preferred organic solvents S1 are selected from xylene and / or methoxypropanol or aliphatic hydrocarbons and methoxypropyl acetate and butyl diglycol acetate and dibasic acid esters.
[0065] The coating composition according to the invention is preferably a coating composition which is liquid at a temperature of 23° C. The coating composition therefore advantageously contains at least one solvent S1 in a total amount of 10 to 95% by weight, preferably 20 to 90% by weight and very preferably 25 to 60% by weight, in each case relative to the total weight of the coating composition.
[0066] Crosslinker CL: The aforementioned preferred binders B generally do not have film-forming properties by themselves, so that when such resins are used, a corresponding crosslinker is additionally used. The coating composition of the present invention therefore preferably further comprises at least one crosslinker CL. The crosslinker CL is preferably selected from the group consisting of amino resins, unblocked polyisocyanates, blocked polyisocyanates, polycarbodiimides, phenalkamine hardeners, polyaminoamide resins, melamine resins, resins containing carboxylic acid groups, beta-hydroxyalkylamides, tris(alkoxycarbonylamino)triazines and mixtures thereof, very preferably phenalkamine hardeners and / or polyaminoamide resins and / or blocked or aromatic polyisocyanates and / or melamine resins.
[0067] When an epoxy resin is used as binder B, the at least one crosslinker CL is preferably selected from phenalkamine and / or polyaminoamide compounds. Phenalkamines and polyaminoamides belong to the general class of "polyamines", a collective term for organic compounds having two or more amino groups, examples of which include diamines or triamines. In addition to the amino groups, the compounds in this case have an aliphatic or aromatic parent structure, i.e., for example, amino and aliphatic groups or amino and aromatic groups (aliphatic or aromatic polyamines). Polyamines may of course contain aliphatic and aromatic units and, in addition, optionally, further functional groups. Examples of aliphatic polyamines include diethylenetriamine, triethylenetetramine, 3,3',5-trimethylhexamethylenediamine, 1,2-cyclohexyldiamine, and isophoronediamine. Examples of aromatic amines include methylenedianiline and 4,4-diaminodiphenylsulfone. The general term "polyamine" also includes organic compounds prepared, for example from aliphatic or aromatic polyamines (so-called base polyamines), by reacting at least a portion of their amino groups with other organic compounds, in order to affect various properties such as the reactivity and / or solubility of the compound and / or to affect the properties of the coatings produced from the coating composition in question (for example surface hardness). Such compounds therefore constitute adducts and, if they still contain at least two amino groups, are defined as polyamine adducts or modified polyamines. They have, of course, a higher molecular weight than the aforementioned polyamines, and therefore also less adverse health effects. Such polyamine adducts often constitute the reaction products of aliphatic and / or aromatic polyamines with polyepoxides, for example the epoxy resins mentioned above, or individual difunctional compounds, such as bisphenol A diglycidyl ether, in which a stoichiometric excess of amino groups compared to the epoxide groups is used. These adducts are used to cure the epoxy resins in the actual coating compositions.One known example is the reaction product of 3,3',5-trimethylhexamethylenediamine as the base polyamine and diglycidyl ether of bisphenol A as the epoxy resin. Also included under the general term "polyamine" are, for example, conventional polyaminoamides, which are polymers prepared by condensation of, for example, the aforementioned polyamines as the base polyamines and polycarboxylic acids, more particularly dicarboxylic acids.
[0068] In one or more embodiments, at least one crosslinker CL, preferably a polyamine, has an amine number of 100-300 mg KOH / g solids, preferably 140-200 mg KOH / g solids, determined according to DIN 16945:1989-03.
[0069] It is even more preferred if the at least one crosslinker CL, preferably a polyamine, has an active H equivalent mass (active hydrogen (NH group), i.e. mass of polyamine per mole of hydrogen on primary and secondary amino groups) of 15 to 400 g / equivalent solids, more particularly of 150 to 300 g / equivalent solids (measured according to the method for determination of primary and secondary amine groups in accordance with ASTM D2073).
[0070] Such polyamines or polyamine adducts, or polyaminoamides, as reactants and / or crosslinkers for epoxy resins are available, for example, from Cytec under the trade name Beckopox, or from Cardolite under the trade name Cardolite (eg Cardolite NC-562).
[0071] If OH-functional resins, such as polyesters or OH-functional polyurethanes, are used as binders B, the at least one crosslinker CL is preferably selected from free and / or blocked polyisocyanates based on hexamethylene diisocyanate or isophorone diisocyanate and / or melamine resins. Such blocked polyisocyanates preferably have an unblocking temperature of 110-185°C, very preferably 135-155°C, and can therefore be completely unblocked at curing temperatures of 180-240°C. Suitable polyisocyanates include, but are not limited to, alkylene polyisocyanates such as hexamethylene diisocyanate, 4- and / or 2,4,4-trimethylhexamethylene diisocyanate, dodecamethylene diisocyanate, 1,4-diisocyanatocyclohexane, 1-isocyanato-3,3,5-trimethyl-5-isocyanatomethylcyclohexane (isophorone diisocyanate), 2,4'- and / or 4,4'-diisocyanatodicyclohexylmethane, 3-isocyanato-methyl-3,5,5-trimethylcyclohexylisocyanate, aromatic polyisocyanates such as 2,4'- and / or 4,4'-diisocyanatodiphenylmethane, 2,4- and / or 2,6-diisocyanatotoluene, naphthylene diisocyanate, and mixtures of these polyisocyanates. Generally, polyisocyanates having an average of three or more isocyanate groups are used, which may be derivatives or adducts of diisocyanates. Useful polyisocyanates are obtained by reacting an excess of isocyanates with water, polyols (e.g. ethylene glycol, propylene glycol, 1,3-butylene glycol, neopentyl glycol, 2,2,4-trimethyl-1,3-pentanediol, hexamethylene glycol, cyclohexanedimethanol, hydrogenated bisphenol A, trimethylolpropane, trimethylolethane, 1,2,6-hexanetriol, glycerin, sorbitol or pentaerythritol), or by reacting the isocyanates with themselves to produce isocyanurates.Furthermore, biuret-, isocyanurate-, urethane-, carbodiimide-, allophanate- and uredione-containing polyisocyanates can be used. Particularly preferably, hexamethylene diisocyanate or isophorone diisocyanate and blocked polyisocyanates based on hexamethylene diisocyanate or isophorone diisocyanate are used.
[0072] The at least one blocked polyisocyanate preferably has an NCO content of 4 to 12%, more preferably 4 to 10% and very preferably 4.6 to 8.6%, in each case based on the solids content.
[0073] The melamine resin is preferably selected from melamine resins etherified with methanol, ethanol, propanol and / or butanol, preferably with methanol, and contains on average 0.05 to 3, preferably 0.07 to 2.5, very preferably 0.08 to 2 imino groups.
[0074] Preferably, the coating composition contains at least one crosslinker CL in a total amount of 1-30% by weight, preferably 5-20% by weight, very preferably 10-15% by weight, in each case relative to the total weight of the coating composition. The use of the aforementioned crosslinkers in the amounts stated results in sufficient crosslinking of the coating composition of the invention, thus supporting the corrosion-inhibiting properties of the graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof.
[0075] Curing catalyst: To accelerate the cure time, the coating composition of the present invention may further include at least one curing catalyst.
[0076] Suitable curing catalysts are selected from the group consisting of functionalized phenols, tin(IV) compounds, bismuth compounds, blocked or unblocked sulfonic acid compounds and mixtures thereof, preferably 2,4,6-tris(dimethylaminomethyl)phenol or tin(IV) alkoxylates and / or sulfonic acid compounds. Suitable sulfonic acid compounds are selected from dinonylnaphthalene monosulfonic acid, dinonylnaphthalene disulfonic acid and / or docecylbenzene sulfonic acid.
[0077] The coating composition preferably contains at least one curing catalyst in a total amount of 0.05 to 5% by weight, more preferably 0.1 to 3% by weight, very preferably 0.3 to 2.5% by weight, in each case relative to the total weight of the coating composition.
[0078] Pigments / fillers: The coating composition of the present invention may further comprise at least one pigment and / or filler. The pigment may be selected from color pigments, effect pigments, and corrosion-inhibiting pigments known to those skilled in the art.
[0079] The term "pigment" is known to the skilled artisan, for example from DIN 55945 (date: October 2001). "Pigments" in the sense of the present invention preferably refer to powder or platelet-shaped compounds that are substantially, preferably completely insoluble in the medium that surrounds them, for example the coating composition of the present invention. Pigments as defined herein differ from "fillers" at least in their refractive index, which for pigments is ≧1.7.
[0080] Suitable pigments are preferably selected from the group consisting of organic and inorganic color-imparting pigments (including black and white pigments), effect pigments, and mixtures thereof.
[0081] Examples of suitable inorganic color-imparting pigments are white pigments, such as zinc white, zinc sulfide or lithopone, black pigments, such as carbon black, iron manganese black or spinel black, chromatic pigments, such as chromium oxide, chromium oxide hydrate green, cobalt green or ultramarine green, cobalt blue, ultramarine blue or manganese blue, ultramarine violet or cobalt violet and manganese violet, red iron oxide, cadmium sulfoselenide, molybdate red or ultramarine red, brown iron oxide, mixed brown, spinel phase and corundum phase or chrome orange, or yellow iron oxide, nickel titanium yellow, chrome titanium yellow, cadmium sulfide, cadmium zinc sulfide, chrome yellow, or bismuth vanadate. Examples of further inorganic color-imparting pigments are, for example, aluminum oxide, aluminum oxide hydrate, in particular boehmite, titanium dioxide, zirconium oxide, cerium oxide, and mixtures thereof. Examples of suitable organic color-imparting pigments are monoazo pigments, disazo pigments, anthraquinone pigments, benzimidazole pigments, quinacridone pigments, quinophthalone pigments, diketopyrrolopyrrole pigments, dioxazine pigments, indanthrone pigments, isoindoline pigments, isoindolinone pigments, azomethine pigments, thioindigo pigments, metal complex pigments, perinone pigments, perylene pigments, phthalocyanine pigments or aniline black. Effect pigments include not only metallic effect pigments but also pearlescent pigments, etc.
[0082] The term "filler" is known to the skilled artisan, for example from DIN 55945 (date: October 2001). "Filler" in the sense of the present invention preferably refers to a substance that is substantially insoluble, preferably completely insoluble, in the coating composition of the present invention, and is more particularly used to increase the volume. "Filler" in the sense of the present invention differs from "pigments" at least in its refractive index, which for fillers is <1.7. Any conventional filler known to the skilled artisan may be used. Examples of suitable fillers are kaolin, dolomite, calcite, chalk, calcium sulfate, barium sulfate, graphite, silicates, such as magnesium silicate, more particularly corresponding phyllosilicates, such as hectorite, bentonite, montmorillonite, talc and / or mica, silica, more particularly fumed silica, hydroxides, such as aluminum hydroxide or magnesium hydroxide, or organic fillers, such as textile fibers, cellulose fibers, polyethylene fibers, or polymer powders. For further details, see "Filler" in Römpp Lexikon Lacke und Druckfarben, Georg Thieme Verlag, 1998, pp. 250ff.
[0083] While the above pigments and fillers are suitable for use in the coating compositions of the present invention, pigments containing such environmentally problematic elements, such as Pb, Cd, Cr, Cu, Mo, Hg, Se or Zn, are less preferred and most preferably are not included in the coating compositions of the present invention.
[0084] The at least one pigment and / or filler is preferably contained in a total amount of 10 to 70% by weight, more preferably 20 to 60% by weight, very preferably 35 to 50% by weight, in each case relative to the total weight of the coating composition. If one or more pigments and / or fillers are present in the coating composition of the invention, the aforementioned amounts are relative to the sum of the amounts of all pigments and / or fillers contained in said coating composition.
[0085] If the coating composition of the present invention contains at least one colour pigment, such as titanium dioxide, iron oxide, zinc oxide or an organic pigment, such pigment is preferably present in a total amount of 5 to 20% by weight, more preferably 5 to 15% by weight and very preferably 7.5 to % by weight, in each case relative to the total weight of the coating composition.
[0086] Suitable amounts of the corrosion-inhibiting pigment are 2 to 10% by weight, preferably 4 to 8% by weight, very preferably 4 to 6% by weight, in each case based on the total weight of the coating composition.
[0087] The coating composition preferably comprises a pigment to binder ratio of from 10:1 to 1:10, more preferably from 6:1 to 1:6, even more preferably from 5:1 to 1:2, very preferably from 7:3 or 2:1 to 1:2.
[0088] Additives: The coating composition may further contain at least one additive commonly used in aqueous and solvent-based coating compositions.Suitable coating additives are selected from the group consisting of (i) UV absorbers, (ii) light stabilizers, such as HALS compounds, benzotriazoles or oxalanilides, (iii) rheology modifiers, such as sag control agents (urea crystal modified resins), organic and inorganic thickeners, (iv) free radical scavengers, (v) lubricants, (vi) polymerization inhibitors, (vii) defoamers, (viii) wetting agents, (ix) fluorine compounds, (x) adhesion promoters, (xi) leveling agents, (xii) film-forming aids, such as cellulose derivatives, (xiii) flame retardants, and (xiv) mixtures thereof.
[0089] Examples of suitable wetting agents are polycarboxylic acid polymers, high molecular weight block copolymers, acrylic copolymers, unsaturated polyamines, carboxylic acid esters and mixtures thereof. The wetting agents are typically contained in a total amount of 0.1 to 1.5% by weight, preferably 0.2 to 0.5% by weight, in each case based on the total weight of the coating composition.
[0090] Suitable defoamers are silicone-free polymers, polymethylalkylsiloxanes, polysiloxanes, acrylic resins, and mixtures thereof, having defoaming properties. The defoamers are typically contained in a total amount of 0.1 to 1.5% by weight, very preferably 0.25 to 0.75% by weight, in each case based on the total weight of the coating composition.
[0091] The abovementioned further additives are preferably used in customary amounts, for example from 0.1 to 20% by weight, based on the total weight of the coating composition.
[0092] In one or more specific embodiments, the coating composition of the present invention is completely free of chromium-containing corrosion inhibitors. In a more highly specific embodiment, the coating composition of the present invention is completely free of chromium and chromium-containing substances, i.e., free of even the slightest traces and impurities of chromium and chromium-containing substances, and very preferably, the content of said substances is 0% by weight, based on the total weight of the coating composition.
[0093] Properties of the coating composition of the present invention: When the coating composition of the present invention is a composition to be applied by spraying, it preferably has a Ford viscosity in a DIN 4 cup at 20° C. of 15 to 50 seconds, more preferably 20 to 45 seconds, and most preferably 25 to 40 seconds.
[0094] When the coating composition of the present invention is formulated as a dip coating composition, the composition preferably has a temperature of 23° C. and a shear rate of 150 s -1The viscosity at is 200 to 1,000 mPa*s, very preferably 500 to 800 mPa*s, determined in accordance with DIN EN ISO 3219:1994-10 and DIN 53019-2:2001-02.
[0095] When the coating composition of the present invention is formulated as a primer coating composition suitable for coil coating, the composition preferably has a viscosity of 12-120 s per 4 mm, as determined according to DIN 53211-4.
[0096] The solids content of the coating composition of the present invention may vary according to the requirements of the individual case. The solids content is mainly guided by the viscosity required for application and may be adjusted by a person skilled in the art based on his general technical knowledge. Preferably, the coating composition of the present invention has a solids content of 20-90% by weight, more particularly 30-80% by weight, and more particularly 40-60% by weight or 50-70% by weight, determined according to DIN EN ISO3251:2008-06.
[0097] The coating composition of the present invention can be formulated as a primer coating composition, a primer-surfacer coating composition, a filler coating composition, a conversion coating composition, an electrodeposition coating composition or a dip coating composition. Depending on the particular use of the coating composition of the present invention, suitable binders B and solvents S1 are selected to match the film-forming and application properties to the particular intended use.
[0098] The coating compositions of the present invention can be formulated as a one-component system (1C) or a multi-component system, ie, a system comprising at least two separate components.
[0099] In the one-component (1C) system, the components to be crosslinked, e.g. the organic polymer as binder (B) and the crosslinker CL, are present in parallel with one another, i.e. in one component. A prerequisite for this is that the components to be crosslinked react with one another only at relatively high temperatures and / or upon exposure to actinic radiation.
[0100] In a two-component (2C) system, the components to be crosslinked, for example the organic polymer as binder B and the crosslinker CL, are present separately from one another in at least two components, which are mixed immediately before application of the coating composition. This form is selected if the components to be crosslinked react with one another even at room temperature.
[0101] Preferably, the coating composition of the present invention is formulated as a two-component (2C) system. The system preferably contains at least a binder B in a suitable solvent S1 in a first component and at least one crosslinker CL in a suitable solvent S1 in a second component. The graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof can be contained in either the first or second component. Preferably, the graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof is contained in the first component.
[0102] Method for preparing the coating composition of the present invention A further subject of the invention is a method for preparing a coating composition according to the invention, which method comprises the following steps: (a) preparing a dispersion D of at least one graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof in at least one solvent S2, (b) adding the dispersion D prepared in step (a) to a mixture containing at least one binder B and / or at least one silane compound SC and at least one solvent S1; Includes.
[0103] Dispersing at least one graphene oxide containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof (GO-M) in at least one solvent S2 can be performed by adding each of the graphene oxide containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof (GO-M) to at least one solvent S2 and dispersing the graphene oxide containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof (GO-M) by, for example, ultrasonication.
[0104] Dispersion D prepared in step (a) preferably contains at least one graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof in a total amount of 0.05 to 5% by weight, more preferably 1 to 4% by weight, very preferably 1.5 to 3% by weight, in each case relative to the total weight of the dispersion. Said amounts allow the graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof to be dispersed in solvent S2 in a sufficiently high amount, so that the incorporation of the graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof into the coating composition of the invention does not significantly affect the high solids content.
[0105] In step (a), a suitable solvent S2 used for the dispersion of graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof is selected from the group consisting of aliphatic and / or aromatic hydrocarbons, ketones, esters or mixtures thereof, preferably esters, very preferably ethyl acetate.
[0106] Preferably, dispersion D contains at least one solvent S2 in a total amount of 95 to 99.95% by weight, preferably 96 to 99% by weight and very preferably 97 to 98.5% by weight, in each case relative to the total weight of the dispersion. The dispersion prepared in step (a) of the method of the invention thus preferably consists of graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof and of solvent S2.
[0107] Suitable total amounts of dispersion D added in step (b) are 0.1 to 10% by weight, preferably 1 to 7% by weight and very preferably 2 to 4% by weight, in each case relative to the total weight of the prepared coating composition.
[0108] What has been said regarding the coating composition of the invention applies mutatis mutandis with respect to the further preferred embodiments of the method of the invention.
[0109] A method according to the invention for preparing at least one coating layer on a substrate (S): The coating compositions of the present invention and the coating compositions prepared from the methods of the present invention can be used to form a coating layer on a substrate.
[0110] The method according to the invention comprises the following steps: (i) applying a coating composition of the present invention or a coating composition prepared by the method of the present invention directly onto a substrate (S); (ii) forming a film from the coating composition applied in step (i) by curing the coating composition; and (iii) optionally applying at least one further coating composition to the coating layer formed in step (ii) and curing said coating composition. At least one coating layer is formed on the substrate (S) by the above-mentioned steps.
[0111] The substrate (S) is preferably selected from metal substrates, metal substrates coated with a conversion coating, and mixtures thereof. When the coating composition of the present invention comprises at least one silane compound SC, it is preferred if a metal substrate is used in step (i). When the coating composition of the present invention does not contain at least one silane compound SC, a conversion coating layer can be applied to the substrate before carrying out step (i) and a conversion coating composition known in the art can be used to improve the adhesion of the coating composition of the present invention. Particularly preferably, a chromium-free conversion coating composition is used in the method of the present invention, such as Granodine 1455 or zinc phosphate coat. The conversion layer is preferably 20-300 nm thick and can be applied, for example, via a chemcoater or by spraying / squeezing.
[0112] The substrate (S) may be pretreated in any conventional manner, for example by cleaning, before step (i) of the method of the invention or before applying a conversion coating. Cleaning can be achieved mechanically, for example by wiping, sanding and / or polishing, and / or chemically by pickling methods, for example by wet etching in acid or alkaline baths, or by hydrochloric or sulfuric acid. Cleaning with organic solvents or aqueous cleaners is also possible.
[0113] According to a first option, preferred metal substrates are aluminum, aluminum alloys, for example more particularly aluminum-copper alloys from the 2000er, 5000er, 6000er or 7000er series, very preferably AA6014, AA6016, AA6022, AA6111, AA6061, AA7075 and AA5083 alloys, and also unalloyed and alloyed steels commonly used in the automotive field. The substrate itself can be of any shape, for example a simple metal panel or a complex component such as an automotive body and its parts.
[0114] According to a second option, the preferred metal substrate is structural steel, optionally coated with a metal coating and frequently used in coil coating processes. Suitable metal coatings are selected from zinc / iron alloys, zinc / aluminum alloys, aluminum / zinc alloys, zinc / magnesium alloys, zinc / chromium or zinc / nickel alloys, and zinc doped with aluminum.
[0115] Process (i): In step (i) of the method of the present invention, the coating composition of the present invention or the coating composition prepared by the method of the present invention is applied directly onto a substrate. As used herein, the phrase "applied directly to a substrate" means that no other coating material capable of forming an organic-polymer matrix or a conversion coating material is applied in the method of the present invention before applying the coating composition. However, this does not exclude the use of a substrate that already contains a coating layer, such as a conversion coating layer as disclosed above.
[0116] Depending on the substrate, application of the coating composition can be carried out by known techniques, for example by spraying, knife coating, scattering, pouring, dipping, impregnation, trickling or rolling. In the case of metal substrates used in the automotive sector, the techniques of spraying or knife coating are used.
[0117] If the coating composition applied in step (i) is used in a coil coating process, said composition may be applied by spraying, flow coating or roller coating. Of these application techniques, roller coating is particularly advantageous and is therefore preferably used according to the invention. Each application step in roller coating may be carried out using two or more rolls. It is preferred to use 2 to 4, and especially 2, rolls. In roller coating, a rotating pick-up roll is immersed in a reservoir of the coating material according to the invention and picks up the coating material thus applied. This material is transferred by the pick-up roll, either directly or via at least one transfer roll, to a rotating application roll. From this latter roll, the coating material is transferred onto the coil by bidirectional or reverse contact transfer. Alternatively, the coating material according to the invention can also be fed directly into the gap between the two rolls, also called nip feed. According to the invention, reverse contact transfer, i.e. the reverse roller coating process, is advantageous and is therefore preferably used.
[0118] Step (ii): In step (ii) of the method of the present invention, the applied coating composition is cured using known techniques to form a polymer film. Since physically and thermally cured systems are preferred in the context of the present invention, physical or thermal curing is preferred. Particularly preferred is thermal curing of externally crosslinked 2C systems.
[0119] According to the first option, the thermal curing preferably takes place at a temperature of 20-25° C. This rather low curing temperature is possible due to the use of a binder / crosslinker system that is based on epoxy resin / polyamine. The duration of the thermal curing can vary greatly depending on the particular case, for example between 5 minutes and 5 days, more particularly between 50 and 70 minutes.
[0120] According to a second option, curing preferably occurs at temperatures between 140 and 240°C by using convection heat transfer, near or far infrared radiation, and / or electrical induction. Said curing temperatures are preferred in a coil coating process in which a continuous coil having the applied coating composition of the invention thereon passes through a convection oven, the coil reaching a peak metal temperature (PTM) of 200 to 240°C at the end of the oven. The residence time in this oven is typically 20 to 60 seconds, depending on the belt speed and the material of the coil. Preferably, a forced air oven with a length of 30 to 50 m, in particular 35 to 45 m, is used. The temperature of the forced air is preferably below 300°C, in particular below 280°C.
[0121] Curing may be preceded by, depending on the individual case and the binder / crosslinker system used, a flash-off for e.g. 1 to 60 minutes at room temperature (approx. 15 and 25° C.) and / or drying for e.g. 1 to 60 minutes at slightly elevated temperatures of 30 to 80° C. Flash-off and drying in the context of the present invention means the evaporation of the organic solvent and / or water, resulting in a dry but not yet completely crosslinked coating film.
[0122] The dry film thickness of the cured coating layer obtained after step (ii) is preferably 1-100 μm, more preferably 2-90 μm, very preferably 55-75 μm or 3-30 μm. When the method of the invention is used for coating substrates for use in the automotive and aviation sector, higher dry film thicknesses of 15-100 μm are used, whereas for coil coatings, dry film thicknesses of less than 10 μm are preferred.
[0123] Step (iii): In the optional step (iii) of the present invention, at least one further coating composition is applied onto the cured coating film formed in step (ii), and said further coating composition is cured. The coated substrate obtained after step (ii) can be cooled before carrying out step (iii), for example by spraying the coated substrate with water. This is particularly preferred when a high curing temperature is used in step (ii).
[0124] At least one further coating layer is obtained by applying any conventional and known coating material capable of forming a coating layer based on a polymer matrix. For the coating materials overcoated with the coating of the present invention, the application methods described above may also be used, but if they are powder coating materials or electrocoatings, conventional and special application methods are used, such as electrostatic powder spraying for low-speed coils, powder cloud chamber process for high-speed coils, and cathodic electrocoating coating.
[0125] Following application, the coating is cured, likewise by known and customary techniques. The individual coatings can also be produced by applying the individual coats successively, without fully curing each time, and then curing them at the end in a joint curing procedure (wet-on-wet method). It is of course also possible to fully cure the individual coats in each case.
[0126] The method of the present invention preferably comprises applying and curing at least one further coating material to form a multi-layer coating. In the context of the automotive industry, the further coating may be a conventional surfacer coat, base coat and clear coat, as is known. Thus, it is preferred to produce a multi-layer coating consisting of the described coatings, which also comprises at least one surfacer coat, base coat and clear coat, apart from the cured coating layer produced from the coating composition of the present invention. In the context of the coil coating or aviation industry, the at least one further coating composition constitutes, for example, a typical single-coat topcoat composition based on (two-component) polyurethane, polyester, epoxy, melamine or phenolic resin systems. Thus, in an equally preferred variant of the present invention, a multi-layer coating consisting of these two coatings, which also comprises a topcoat, apart from the cured coating layer produced from the coating composition of the present invention, is produced.
[0127] If the further coating material is a surfacer coat, base coat, clear coat or top coat material commonly used in automobiles, the curing in step (iii) is preferably carried out for a period of 20 to 40 minutes at a temperature of 50 to 70° C. The resulting dry film thickness of such surfacer coat and / or base coat and / or clear coat layers is in each case preferably 40 to 100 μm, more preferably 45 to 90 μm and very preferably 50 to 60 μm.
[0128] If the further coating material is a coil coating or a topcoat material used in the aviation industry, the curing in step (iii) is preferably carried out at a temperature of 250-270°C (PMT) in a convection oven as previously described in step (ii). The residence time is preferably about 10-30 seconds, after which the coated substrate may be cooled by spraying water on said substrate. The dry film thickness of the resulting topcoat layer is preferably 1-15 μm, preferably 1-10 μm, very preferably 1-5 μm.
[0129] The coated coils of the present invention can be wound after production and then further processed elsewhere, or can be further processed directly as they come from the coil coating operation. For example, they may be laminated with plastic or provided with a removable protective film. They can also be cut into appropriately sized pieces and then shaped. Examples of suitable shaping methods include pressing and deep drawing.
[0130] What has been said regarding the inventive coating composition and the inventive process for producing said coating composition applies mutatis mutandis with respect to the further preferred embodiments of the inventive process.
[0131] Coating layer or multi-layer coating (MC) of the present invention: The result after completion of step (ii) or (iii) of the method of the present invention is a coating layer or multi-layer coating (MC) of the present invention.
[0132] What has been said about the inventive coating composition, the inventive process for producing the coating composition and the inventive process for producing the coated substrate applies mutatis mutandis with respect to the further preferred embodiments of the inventive coating layer or multi-layer coating.
[0133] Method of using the present invention: A final subject of the invention is the use of at least one graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof in a composition to improve the corrosion protection properties of said composition.
[0134] Preferably, the composition is a coating composition, more preferably an organic coating composition.
[0135] According to an alternative embodiment, the composition is a sealant composition.
[0136] What has been said about the inventive coating composition, the inventive process for producing a coating composition, the inventive process for producing a coated substrate and the inventive coated substrate applies mutatis mutandis with respect to the further preferred embodiments of the inventive process.
[0137] The present invention will be described in particular by the following embodiments: Embodiment 1: a) at least one graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof; b) at least one binder B and / or at least one silane compound SC, and c) at least one solvent S1 1. A coating composition comprising:
[0138] Embodiment 2: A coating composition according to embodiment 1, wherein the monovalent metal ion is lithium.
[0139] Embodiment 3: A coating composition according to embodiment 1 or 2, wherein the coating composition contains at least one graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof, preferably graphene oxide containing lithium ions, in a total amount of 0.1 ppm to 5 wt.-%, preferably 0.1 ppm to 1 wt.-%, more preferably 0.1 ppm to 500 ppm, even more preferably 0.3 to 50 ppm, very preferably 0.35 to 1 ppm, in each case relative to the total weight of the coating composition.
[0140] Embodiment 4: A coating composition according to any of the preceding embodiments, wherein the at least one binder B is selected from the group consisting of (i) poly(meth)acrylates, more particularly hydroxy- and / or carboxylate- and / or amine-functional poly(meth)acrylates, (ii) polyurethanes, more particularly hydroxy- and / or carboxylate- and / or amine-functional polyurethanes, (iii) linear or branched polyesters or polyamide-modified polyesters, more particularly linear or branched polyester polyols, (iv) polyethers, more particularly polyether polyols, (v) polyepoxides, (vi) phenoxy resins, (vii) copolymers of the mentioned polymers, and (vi) mixtures thereof, preferably polyepoxides, linear or branched polyesters and / or polyester polyurethane copolymers.
[0141] Embodiment 5: A coating composition according to any of the preceding embodiments, wherein at least one binder B has an epoxy equivalent weight (EEW) of 100 to 400 g / eq., preferably of 150 to 350 g / eq., very preferably of 200 to 300 g / eq., determined according to DIN EN ISO 3001:1999-11.
[0142] Embodiment 6: A coating composition according to any of the preceding embodiments, wherein the at least one binder B is selected from a mixture of two different polyepoxides, where a first polyepoxide B1 has a dynamic viscosity (determined according to ASTM D445-06) of 0.5 to 2 Pa*s and a second polyepoxide B2 has a dynamic viscosity (determined at a shear rate of 500 1 / s and 23° C. according to DIN EN ISO 3219:1994-10) of 800 to 1400 mPa*s.
[0143] Embodiment 7: A coating composition according to any of embodiments 1 to 4, wherein at least one binder B is selected from linear and / or branched polyesters, preferably linear polyesters.
[0144] Embodiment 8: A coating composition according to embodiment 7, wherein the at least one linear polyester has a weight average molecular weight of 2,000 to 30,000 g / mol, preferably 2,500 to 25,000 g / mol, more preferably 3,000 to 20,000 g / mol, very preferably 3,000 to 17,000 g / mol, determined in accordance with DIN EN ISO 16014-5.
[0145] Embodiment 9: A coating composition according to embodiment 7 or 8, wherein the coating composition comprises at least two different linear polyesters P1 and P2, wherein the polyester P1 has a weight average molecular weight of 2,000 to 9,000 g / mol, preferably 3,000 to 6,000 g / mol, and the linear polyester P2 has a weight average molecular weight of 10,000 to 20,000 g / mol, preferably 14,000 to 16,000 g / mol, the weight average molecular weights being determined in each case according to DIN EN ISO 16014-5.
[0146] Embodiment 10: A coating composition according to embodiment 9, in which the weight ratio of the at least one linear polyester P1 to the at least one polyester P2 is from 2:1 to 1:2, preferably from 2:1 to 1:1.
[0147] Embodiment 11: A coating composition according to any of embodiments 7 to 10, wherein the at least one linear polyester has a hydroxyl number of 20 to 100 mg KOH / g, preferably 30 to 80 mg KOH / g, more preferably 40 to 70 mg KOH / g, determined according to DIN 53240-3:2016-03.
[0148] Embodiment 12: At least one linear polyester has a glass transition temperature T of 30 to 80° C., preferably 40 to 70° C., more preferably 45 to 65° C. g 12. The coating composition according to any of embodiments 7 to 11, wherein the coating composition has a viscosity of 1000 s, as measured according to DIN EN ISO11357-2:2014.
[0149] Embodiment 13: A coating composition according to any of the preceding embodiments, wherein the coating composition comprises at least one binder B, preferably at least one polyepoxide or at least one linear polyester, in a total amount of 1 to 40% by weight solids, preferably 5 to 30% by weight solids, very preferably 15 to 20% by weight solids, in each case relative to the total amount of the coating composition.
[0150] Embodiment 14: A coating composition according to any of the preceding embodiments, wherein the silane compound SC is selected from silane compounds comprising at least one primary amino group and at least one hydrolyzable alkoxy group.
[0151] Embodiment 15: The silane compound SC is represented by the general formula (I) NH2-R 1 -YR 2 -Si(R a ) 3-x (R b ) x (I) (In the formula, R 1 , R 2 are, independently of each other, an alkylene group containing 1 to 10 carbon atoms, R a is an alkoxy group containing 1 to 4 carbon atoms, R b is an alkyl group containing 1 to 4 carbon atoms or an alkoxy group containing 1 to 4 carbon atoms, Y is oxygen, sulfur or NR 3 is a group, R 3 is hydrogen or an alkyl group containing 1 to 4 carbon atoms, and (x is 0 to 1) The coating composition according to any of the preceding embodiments, having the following structure:
[0152] Embodiment 16: R 1 is a C2 alkylene group, and / or R 2A coating composition according to embodiment 15, wherein is a C alkylene group.
[0153] Embodiment 17: R a 17. The coating composition according to embodiment 15 or 16, wherein is an alkoxy group containing 1 carbon atom and x is 0.
[0154] Embodiment 18: A coating composition according to any of embodiments 15 to 17, wherein Y is an NH group.
[0155] Embodiment 19: A coating composition according to any of the preceding embodiments, comprising at least one silane compound SC, preferably a silane compound of general formula (I), in a total amount of 2 to 20% by volume, preferably 5 to 15% by volume, in each case relative to the total volume of the coating composition.
[0156] Embodiment 20: A coating composition according to any of the preceding embodiments, wherein the solvent S1 is selected from the group consisting of water, aliphatic and / or aromatic hydrocarbons, ketones, esters, or mixtures thereof, preferably water or xylene and / or methoxypropanol or aliphatic hydrocarbons and methoxypropyl acetate and butyl diglycol acetate and dibasic acid esters.
[0157] Embodiment 21: A coating composition according to any of the preceding embodiments, which contains at least one solvent S1 in a total amount of 10 to 95% by weight, preferably 20 to 90% by weight, very preferably 25 to 60% by weight, in each case relative to the total weight of the coating composition.
[0158] Embodiment 22: A coating composition according to any of the preceding embodiments, further comprising at least one crosslinker CL selected from the group consisting of amino resins, unblocked polyisocyanates, blocked polyisocyanates, polycarbodiimides, phenylalkamine hardeners, polyaminoamide resins, melamine resins, resins containing carboxylic acid groups, beta-hydroxyalkylamides, tris(alkoxycarbonylamino)triazines and mixtures thereof, very preferably phenylalkamine hardeners and / or polyaminoamide resins and / or blocked or aromatic polyisocyanates and / or melamine resins.
[0159] Embodiment 23: A coating composition according to embodiment 22, wherein at least one crosslinker CL has an amine number of 100-300 mg KOH / g solids, preferably 140-200 mg KOH / g solids, determined according to DIN 16945:1989-03.
[0160] Embodiment 24: A coating composition according to embodiment 22 or 23, wherein at least one crosslinker CL has an active hydrogen equivalent of 15 to 400 g / equivalent solids, preferably 150 to 300 g / equivalent solids.
[0161] Embodiment 25: A coating composition according to embodiment 24, in which at least one crosslinker CL is selected from blocked polyisocyanates based on hexamethylene diisocyanate or isophorone diisocyanate and / or melamine resins.
[0162] Embodiment 26: A coating composition according to embodiment 25, wherein the at least one blocked polyisocyanate has an NCO content of 4 to 12%, preferably 4 to 10%, more preferably 4.6 to 8.6%, in each case based on the solids content.
[0163] Embodiment 27: A coating composition according to embodiment 25 or 26, wherein the melamine resin is selected from melamine resins etherified with methanol, ethanol, propanol and / or butanol, preferably with methanol, and contains on average 0.05 to 3, preferably 0.07 to 2.5, very preferably 0.08 to 2 imino groups.
[0164] Embodiment 28: A coating composition according to any of embodiments 22 to 27, comprising at least one crosslinker CL in a total amount of 1 to 30% by weight, preferably 5 to 20% by weight, very preferably 10 to 15% by weight, in each case relative to the total weight of the coating composition.
[0165] Embodiment 29: A coating composition according to any of the preceding embodiments, further comprising at least one curing catalyst.
[0166] Embodiment 30: A coating composition according to embodiment 29, wherein the at least one curing catalyst is selected from the group consisting of functionalized phenols, tin(IV) compounds, bismuth compounds, blocked or unblocked sulfonic acid compounds and mixtures thereof, preferably 2,4,6-tris(dimethylaminomethyl)phenol or tin(IV) alkoxylates and / or blocked dinonylnaphthalenesulfonic acids.
[0167] Embodiment 31: A coating composition according to embodiment 29 or 30, comprising at least one curing catalyst in a total amount of 0.05 to 5% by weight, preferably 0.1 to 3% by weight, very preferably 0.3 to 2.5% by weight, in each case relative to the total weight of the coating composition.
[0168] Embodiment 32: A coating composition according to any of the preceding embodiments, further comprising at least one pigment and / or filler.
[0169] Embodiment 33: A coating composition according to embodiment 32, wherein the at least one pigment and / or filler is selected from the group consisting of: (i) white pigments, such as titanium dioxide, zinc white, colored zinc oxide, zinc sulfide, lithopone; (ii) black pigments, such as black iron oxide, iron manganese black, spinel black, carbon black; (iii) colored pigments, such as ultramarine green, ultramarine blue, manganese blue, ultramarine violet, manganese violet, red iron oxide, molybdate red, ultramarine red, brown iron oxide, mixed brown, spinel and corundum phases, yellow iron oxide, bismuth vanadate; (iv) filler pigments, such as silicon dioxide, silicon oxide, magnesium oxide, kaolin, quartz flour, aluminum oxide, aluminum hydroxide, natural mica, clay, natural and precipitated chalk, talc, barium sulfate, barite; (v) corrosion inhibitor pigments, such as calcium modified silica pigments, zinc phosphate, aluminum phosphate, aluminum triphosphate, silica magnesium pigments; (vi) mixtures thereof.
[0170] Embodiment 34: A coating composition according to embodiment 32 or 33, comprising at least one pigment and / or filler in a total amount of 10 to 70% by weight, preferably 20 to 60% by weight, very preferably 35 to 50% by weight, in each case relative to the total weight of the coating composition.
[0171] Embodiment 35: A coating composition according to any of embodiments 32 to 34, comprising a pigment to binder ratio of 10:1 to 1:10, more preferably 6:1 to 1:6, even more preferably 5:1 to 1:2, and very preferably 7:3 or 2:1 to 1:2.
[0172] Embodiment 36: A coating composition according to any of the preceding embodiments, further comprising at least one coating additive selected from the group consisting of: (i) UV absorbers, (ii) light stabilizers, such as HALS compounds, benzotriazoles or oxalanilides, (iii) rheology modifiers, such as sag control agents (urea crystal modified resins), organic and inorganic thickeners, (iv) free radical scavengers, (v) lubricants, (vi) polymerization inhibitors, (vii) defoamers, (viii) wetting agents, (ix) fluorine compounds, (x) adhesion promoters, (xi) leveling agents, (xii) film forming aids, such as cellulose derivatives, (xiii) flame retardants, and (xiv) mixtures thereof.
[0173] Embodiment 37: A coating composition according to any of the preceding embodiments, wherein the content of chromium and chromium-containing compounds is 0 wt.%, based on the total weight of the coating composition.
[0174] Embodiment 38: A coating composition according to any of the preceding embodiments, having a Ford viscosity in DIN 4 cup at 20° C. of 15 to 50 seconds, preferably 20 to 45 seconds, and highly preferably 25 to 40 seconds.
[0175] Embodiment 39: A coating composition according to any of the preceding embodiments, having a viscosity at 23° C. and a shear rate of 150 s-1 of 200 to 1,000 mPa*s, preferably 500 to 800 mPa*s, determined according to DIN EN ISO 3219:1994-10 and DIN 53019-2:2001-02.
[0176] Embodiment 40: A coating composition according to any of embodiments 1 to 39, having a viscosity, determined according to DIN 53211-4, of 12 to 120 s per 4 mm.
[0177] Embodiment 41: A coating composition according to any of the preceding embodiments, which is a primer coating composition, a primer-surfacer coating composition, a filler coating composition, a conversion coating composition, an electrodeposition coating composition, or a dip coating composition.
[0178] Embodiment 42: A method comprising the steps of: (a) preparing a dispersion D of at least one graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof in at least one solvent S2, (b) adding the dispersion D prepared in step (a) to a mixture containing at least one binder B and / or at least one silane compound SC and at least one solvent S1; 42. A method for preparing a coating composition according to any of the preceding embodiments, comprising:
[0179] Embodiment 43: The process according to embodiment 42, wherein dispersion D contains at least one graphene oxide (GO-M) comprising at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof, in a total amount of 0.05 to 5% by weight, preferably 1 to 4% by weight, very preferably 1.5 to 3% by weight, in each case relative to the total weight of the dispersion.
[0180] Embodiment 44: The process according to embodiment 42 or 43, wherein the solvent S2 is selected from the group consisting of aliphatic and / or aromatic hydrocarbons, ketones, esters or mixtures thereof, preferably esters, very preferably ethyl acetate.
[0181] Embodiment 45: The process according to any of embodiments 42 to 44, wherein the dispersion D contains at least one solvent S2 in a total amount of 95 to 99.95% by weight, preferably 96 to 99% by weight, very preferably 97 to 98.5% by weight, in each case relative to the total weight of the dispersion.
[0182] Embodiment 46: The method according to any of embodiments 42 to 45, wherein Dispersion D is added in a total amount of 0.1 to 10% by weight, preferably 1 to 7% by weight, very preferably 2 to 4% by weight, in each case relative to the total weight of the prepared coating composition.
[0183] Embodiment 47: (i) applying a coating composition according to any one of claims 1 to 41 or a coating composition prepared by a method according to any one of claims 42 to 46 onto a substrate (S), (ii) forming a film from the coating composition applied in step (i) by curing the coating composition; and (iii) optionally applying at least one further coating composition to the coating layer formed in step (ii) and curing said coating composition. A method for forming at least one coating layer on a substrate (S), comprising:
[0184] Embodiment 48: The method according to embodiment 47, wherein the substrate (S) is selected from metal substrates, metal substrates coated with a conversion coating, and mixtures thereof.
[0185] Embodiment 49: The method according to embodiment 47 or 48, wherein the curing in step (ii) is carried out at a temperature of 20-25° C. for a period of 50-70 minutes, or at a temperature of 140-240° C. for a period of 20-60 seconds.
[0186] Embodiment 50: The process according to any of embodiments 47 to 49, wherein the dry film thickness obtained after step (ii) is from 1 to 100 μm, preferably from 2 to 90 μm, very preferably from 55 to 75 μm or from 3 to 30 μm.
[0187] Embodiment 51: (iii) The method according to any of embodiments 47 to 50, wherein at least one further coating layer is applied to the cured coating film formed in step (ii), and the further coating layer is cured separately or simultaneously.
[0188] Embodiment 52: The method according to embodiment 51, wherein the curing in step (iii) is carried out at a temperature of 50-70° C. for a period of 20-40 minutes, or at a temperature of 200-300° C. for a period of 10-30 seconds.
[0189] Embodiment 53: The method according to embodiment 51 or 52, wherein the dry film thickness of at least one further coating layer is from 1 to 100 μm, preferably from 1 to 90 μm, very preferably from 50 to 60 μm or from 1 to 5 μm.
[0190] Embodiment 54: A coating layer or multi-layer coating (MC) produced by the method according to any of embodiments 47 to 53.
[0191] Embodiment 55: A method of using at least one graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof in a composition to improve the corrosion protection properties of said composition.
[0192] Embodiment 56: The method of use according to embodiment 55, wherein the composition is a coating composition, preferably an organic coating composition.
[0193] Embodiment 57: The method of use according to embodiment 55, wherein the composition is a sealant composition. EXAMPLES
[0194] The present invention will be described in further detail by using useful examples, but is in no way limited to these useful examples. Furthermore, the terms "parts", "%" and "ratio" in the examples refer to "parts by mass", "% by mass" and "ratio by mass", respectively, unless otherwise specified.
[0195] 1. Determination method 1.1 Raman spectroscopy The structure of the produced graphene oxide was determined by Raman spectroscopy using a Raman spectrometer RAM ARAMIS manufactured by Horiba Jobin Yvon Lab. An excitation wavelength of 532 nm (green laser) was used, and the exposure time was 20 seconds, repeated three times. A 10% filter was used for the measurement.
[0196] 1.2 ICP-OES analysis The concentrations of monovalent or polyvalent metal ions present in the graphene oxide were determined by ICP-OES using a Spectro Cirros CCD ICP-OES instrument from Spectro Smart and the program Smart Analyzer. The following spectral lines were applied for the different cations: Ca 2+ = 183 nm, K + = 404 nm, Li + = 460 nm, Mg 2+ = 279 nm, Na + = 330 nm, Zn 2+ = 206 nm, Fe 2+ = 238 nm, Al 3+ =396 nm.
[0197] For this purpose, the concentration of each metal ion present in the filtrate obtained after filtration of each graphene oxide containing at least one monovalent metal ion was determined via ICP-OES and compared with the concentration of the metal ion salt solution used for the preparation of each graphene oxide containing at least one monovalent metal ion. The difference between the concentration of the metal ion salt solution used for the preparation of each graphene oxide containing at least one monovalent metal ion and the metal ion concentration in the filtrate directly corresponded to the concentration of the metal ion present in the graphene oxide.
[0198] 1.3 Acetic acid salt spray mist test judgment according to DIN EN ISO9227AASS The acetate salt spray mist test was used to determine the corrosion protection properties of coatings on substrates. According to DIN EN ISO 9227 (date: June 2017), the acetate salt spray mist test was carried out on aluminum substrates, e.g. aluminum AA6014. In this test, the investigated specimen was in a chamber where it was continuously misted with a 5% salt solution with a controlled pH in the range of 3.1-3.3 at a temperature of 35°C for a duration of 1008 hours. The mist was deposited on the investigated specimen, covering it with a corrosive film of salt water.
[0199] Prior to the acetate salt mist test according to DIN EN ISO 9227AASS, the coatings of the investigated samples were scored with a knife down to the substrate so that the level of undermining of the investigated samples could be investigated according to DIN EN ISO 4628-8 (date: 01.03.2013). During the salt mist test according to DIN EN ISO 9227AASS, the substrate corrodes along the score line. As a result of the corrosion process the coating is more or less corroded during the test. The degree of corrosion [mm] is a measure of the resistance of the coating to corrosion. The average corrosion level given in the results below represents the average of the individual values evaluated for two different panels and the individual value of a panel is the average of the corrosion levels at 5 measuring points on the panel.
[0200] 2. Preparation of lithium ion-containing graphene oxide (GO@Li) and dispersion D 2.1 Preparation of lithium ion-containing graphene oxide (GO@Li) Graphene oxide was produced by electrochemical exfoliation of graphite in a two-electrode cell at room temperature using a Statron 3252.1 power supply as follows. First, a graphite rod (10 cm long, 1 cm diameter) and a platinum mesh electrode were placed in a 1 M NaOH solution to pretreat the graphite for 10 min. A voltage of 10 V was applied between the electrodes, with the positive terminal being the graphite (anode). The solution was then exchanged for 0.5 M sulfuric acid and electrolysis was carried out for 1 h with applied voltages between 1 V and 10 V varying by 1 V each. The resulting dark grey solution was then sonicated for 2 h and filtered (pore size 0.45 μm). The residue was collected, washed repeatedly with water and dried at 60 °C.
[0201] The residue obtained was examined for the presence or absence of graphene oxide and any graphite by Raman spectroscopy as described in section 1.1. Generally, the G band (1595 cm -1 around 1350cm -1 A Raman spectrum with the G band and D bands at the same height (around 100 nm) is considered to be indicative of graphene oxide, while a Raman spectrum with the G band higher than the D band is considered to be indicative of graphite. The Raman spectrum obtained from the residue is characteristic of graphene oxide, as it shows G and D bands of virtually equal intensity.
[0202] 0.1 g of the graphene oxide prepared above was placed in a 50 ml test tube. 50 ml of 0.1 M concentrated lithium salt solution was added, and the mixture was sonicated for 24 hours. After filtration (pore size 0.45 μm) and drying at 60 °C, graphene oxide containing lithium ions was obtained. As determined by ICP-OES as described in section 1.2, the graphene oxide prepared contained approximately 1.8 mmol of lithium ions.
[0203] 2.2 Preparation of Dispersion D containing GO@Li The graphene oxide containing lithium ions (GO@Li) prepared in section 2.1 was dispersed in a suitable amount of ethyl acetate to prepare dispersion D containing graphene oxide with lithium ions in solvent S2 (the amounts of GO@Li and ethyl acetate used in the preparation of dispersion D are shown in section 3 and Table 1).
[0204] 3. Preparation of conversion coating layer A galvanized steel panel was degreased with a 60 g / l ENPREP144 solution at 60 °C for 4 min, then rinsed with tap water for 2.5 min and distilled water for 2.5 min at room temperature. 2.7 ml of the dispersion D (1 mg GO@Li per ml ethyl acetate) prepared according to section 2.2 and 100 ml of GO@Li with general formula (I) (R 1 is a C2 alkylene group, R 2 is a C3 alkylene group, R a A coating composition was prepared by mixing a 10 V% solution of a silane compound SC (wherein GO is an alkoxy group containing one carbon atom, x is 0, and Y is an NH group) in a suitable organic solvent. A degreased galvanized steel panel was treated with this coating composition for 1 min at room temperature and then dried at 80 °C for 10 min to obtain a steel panel with a conversion coating layer containing at least one lithium ion-functionalized graphene oxide (GO@Li).
[0205] 4. Preparation of Coating Compositions F1-F3 Coating compositions F1 to F3 were prepared by mixing each of compositions F1-1 to F3-1 with hardener H and diluting the mixture with the commercial product Glasurit 352-216 (available from BASF Coatings GmbH) described below.
[0206] 4.1 Preparation of base varnishes F1-1, F1-2 and F1-3 Base varnishes F1-1 to F3-1 were prepared by the following general procedure. First, items 1-2 in Table 1 were premixed, and items 2-4 were added with stirring at 1000-1500 rpm. After addition was complete, stirring was continued at 1500 rpm for 10 minutes. The remaining ingredients in the amounts listed in Table 1 were then added, and the resulting mixture was stirred for 20 minutes with a high speed dissolver stirrer. The mixture was then dispersed in a small laboratory mill for 1-1.5 hours to a Hegmann value of 22-23 μm. If necessary, additional methoxypropanol was added after milling (see item 13 in Table 1).
[0207] [Table 1]
[0208] * Invention examples 1) Exemplary commercial product: Epikote 834-X-80 (made from bisphenol A and epichlorohydrin, 80% solids solution in xylene, EEW=235-263 g / Eq, kinematic viscosity=1 Pa*s (ASTM D445-06)) (supplied by Hexion) 2) Exemplary commercial product: Beckopox EM460 (bisphenol A, made from phenol and bisphenol A diglycidyl ether, 60% solids solution in isobutanol / xylene, dynamic viscosity = 800-1400 mPa*s (500 1s, 23°C, DIN EN ISO3219)) (supplied by Allnex) 3) Exemplary commercial product: Disperbyk 161 (30% solids in methoxypropyl acetate / butyl acetate) (supplied by Byk Chemie GmbH) 4) Exemplary commercial product: Schwerspat EWO Normal (oil number = 11) (supplied by Sachtleben Minerals) 5) Exemplary commercial product: Luzenac 10M0 (oil number = 48) (supplied by Imerys Performance Additives) 6)Dispersion of 0.3 g graphene oxide in 15.91 g ethyl acetate 7) Dispersion of 0.3 lithium ion-containing graphene oxide (GO@Li) in 12.81 g of ethyl acetate 8) Exemplary commercial product: Titan Rutil R-900-28WP (oil number = 15, supplied by Titanos)
[0209] 4.2 Hardener composition H Curing agent H was prepared by mixing 49.6 grams of Cardolite NC562 (addition type phenalkamine curing agent, solids 65%, amine number = 185, active hydrogen equivalent = 174, supplied by Cardolite), 13.143 grams of Merginamid L190 / 70 (reactive polyaminoamide resin, solids 70%, amine number = 155-185, active hydrogen equivalent = 340, supplied by HOBUM Oleochemicals GmbH), 1.2 grams of diethylenetriamine and 0.4 grams of Ancamine K54 (curing catalyst, tris-2,4,6-dimethylaminomethylphenol, supplied by Ebonik Industries AG).
[0210] 4.3 Coating compositions F1 to F3 Coating compositions F1 to F3 were prepared by mixing each of the base varnishes F1-1 to F1-3 with the hardener H and diluting each mixture with the commercial product Glasurit 352-216 (available from BASF Coatings GmbH) to a spray viscosity of 21 seconds (DIN 4 cup, 20° C.).
[0211] [Table 2]
[0212] * Invention examples
[0213] 4.4 Further Coating Composition Material Ingredients and Properties 4.4.1 Primer Coating Composition
[0214] [Table 3]
[0215] 1) Exemplary commercial product: URALAC SN989S1F-60 (saturated polyester resin, 60% in 30% solvent naphtha and 10% 1-methoxy-2-propanyl acetate) 2) Exemplary Commercial Product: Epikote 834-X-80 (an epoxy resin made from bisphenol A and epichlorohydrin, supplied as an 80% solids solution in xylene) 3) Exemplary commercial products: ALBERDING K U9000VP, 35% ig i.WA or ALBERDING K4820, 35% ig i.WA (Polyurethane dispersion, OH-functional) 4) Exemplary commercial products: ALBERDINGK AC2403, 47% ig i.WA (acrylic dispersion, OH functional, OH content 1.8% on solids) 5) Exemplary commercial product: ALBERDINGK AC2486, 48% ig i.WA (acrylic dispersion) 6) Exemplary commercial product: Cymel 303, 98% ig (melamine resin HMMM) 7) Exemplary commercial products: VESTANADT EP-DS1205, 42%ig i.WA (blocked isocyanate resin, aliphatic, NOC content: 4.6% on solids) or Vestanat EP-DS1076 (blocked isocyanate resin, aliphatic) 8) Exemplary commercial products: Desmodur BL3370 (blocked aliphatic polyisocyanate based on hexamethylene diisocyanate, 70%) 9) Exemplary commercial product: Titandioxid 2310 10)Exemplary commercial product: Aerosil 200 11) Exemplary commercial product: Shieldex C303 (calcium silicate) 12) Exemplary commercial product: Heucophos ZPO (zinc phosphate) 13) The amounts are based on the solids of each of the material components.
[0216] The coating compositions listed in Table 3 can further contain additives and fillers commonly used in primer coating compositions.
[0217] Preferred parameters of the above primer coating composition: Solids content: 20 - 70 mass% Pigment to binder ratio: 1.00:0.05 - 2.00 Viscosity: 1,000 - 10,000 mPa*s Density: 1.050 - 1.400 g / cm 3 .
[0218] Preparation of the cured coating layer using the above primer coating composition: Suitable substrates: Z (hot-dip galvanized steel), ZE (electro-galvanized steel), ZM (zinc-magnesium coated steel) Pretreatment: Granodine 1455 (pH value 2.0 - 2.5, coating mass < 8 mgTi / m 2 ) Curing temperature (PMT, peak metal temperature): 200 - 250 °C Dwell time: 20 - 60 seconds.
[0219] Preferred parameters of the cured primer layer: Dry film thickness: 0.50 - 30.00 μm Solid density: 1.05 - 2.00 g / cm 3 Elastic modulus: T-0~1 (Tesa tear), <T-1 no cracking (judged by T-bending) Crosslinked (MEK-DH, resistance to methyl ethyl ketone according to OENORM EN13523-11): <50 DH (>100 MEK-DH after curing and with topcoat) Glossiness:<50 / 60°(Matte-Silk-Gloss).
[0220] 4.4.2 Water-soluble primer composition
[0221] [Table 4]
[0222] 1) Exemplary commercial products: PHENODUR PW165, 40WA (modified epoxy resin, OH functional, cationically stabilized) 2) Exemplary commercial products: ALBERDINGK XP27401, 38% ig i.WA (acrylic dispersion, OH functional, OH content 1.8% on solids) 3) Exemplary commercial products: ALBERDING K U9000VP, 35% ig i.WA or ALBERDING K4820, 35% ig i.WA (Polyurethane dispersion, OH-functional) 4) Exemplary commercial products: ALBERDINGK AC2403, 47% ig i.WA (acrylic dispersion, OH functional, OH content 1.8% on solids) 5) Exemplary commercial product: ALBERDINGK AC2486, 48% ig i.WA (acrylic dispersion) 6) Exemplary commercial product: Cymel 303, 98% ig (melamine resin HMMM) 7) Exemplary commercial products: VESTANADT EP-DS1205, 42%ig i.WA (blocked isocyanate resin, aliphatic, NOC content: 4.6% on solids) or Vestanat EP-DS1076 (blocked isocyanate resin, aliphatic) 8)Exemplary commercial product: BAYHYDUR BL XP2706, 40%ig i.WA (blocked isocyanate resin, aliphatic, NOC content: 8.6% based on solids) 9) Exemplary commercial product: Titandioxid 2310 10) Exemplary commercial product: Aerosil R972 11) Exemplary commercial product: Shieldex C303 (calcium silicate) 12) Exemplary commercial product: Heucophos ZPO (zinc phosphate) 13) The amounts are based on the solids content of each ingredient.
[0223] The coating compositions listed in Table 4 may further include additives and fillers commonly used in primer coating compositions.
[0224] Preferred parameters of the water-soluble primer coating composition: Solid content: 10~50% by mass Pigment to binder ratio: 1.00:0.05~2.00 Viscosity: 12~120s / 4mm (DIN53211-4) pH value: 1.50~9.00 Density: 1.050~1.400g / cm 3 .
[0225] Preparation of a cured coating layer using the primer coating composition: Suitable substrates: Z, ZE, ZM Optional pretreatment: Granodine 1455 (pH value 2.0-2.5, coating mass <8mgTi / m 2 ) Curing temperature (PMT): 140~250℃ Residence time: 5~60 seconds.
[0226] Preferred parameters of the cured primer layer: Dry film thickness: 0.20 - 20.00 μm Solid density: 1.05 - 2.00 g / cm 3 Elastic modulus: T - 0~1 (Tesa tear), <T - 1 no cracking (judged by T - bend) Crosslinking (MEK - DH): <50 DH (when using top coat after curing)>100 MEK - DH Gloss: <50 / 60° (mat - silk - gloss).
[0227] 4.4.3 Top coat coating composition
[0228]
Table 5
[0229] 1) Exemplary commercially available products: Dynapol LH830, 60%ig (branched saturated copolyester, Mw = 4000 g / mol) 2) Exemplary commercially available products: Dynapol LH538, 65%ig (branched saturated copolyester, M w = 3000 g / mol) 3) Exemplary commercially available products: Dynapol UB790, 60%ig (linear polyurethane resin, M w = 3000 - 6000) 4) Exemplary commercially available products: Cymel303, 98%ig (melamine resin HMMM) 5) Exemplary commercially available products: Desmodur BL3370, 70%ig (block aliphatic isocyanate) 6) Exemplary commercially available products: Vestanat EP - B1481ND, 65%ig (isocyanate crosslinking agent, blocked with caprolactam) 7) Exemplary commercially available products: Titandioxid2310 8) Exemplary commercially available products: Aerosil R972 9)Exemplary commercially available product: Acematt 810 10) The amount is based on the solid content of each material component.
[0230] The coating compositions listed in Table 5 can further contain additives and fillers commonly used in primer coating compositions.
[0231] Preferred parameters of the topcoat coating composition: Solid content: 50 - 70% by mass Pigment to binder ratio: 1.00:0.50 - 1.50 Viscosity: 1000 - 10000 mPa*s Density: 1.100 - 1.350 g / cm 3 .
[0232] Preparation of the cured coating layer using the primer coating composition: Suitable substrates: Z, ZE, ZM Pretreatment: Granodine 1455 (pH value 2.0 - 2.5, coating mass < 8 mg Ti / m 2 ) Curing temperature (PMT): 200 - 260 °C Residence time: 20 - 60 seconds.
[0233] Preferred parameters of the cured primer layer: Dry film thickness: 10.00 - 30.00 μm Solid density: 1.30 - 1.80 g / cm 3 Elastic modulus: T - 0 (Tesa tear), < T - 1 no crack (judged by T - bend) Crosslinking (MEK - DH): < 100 DH Gloss: 20 - 90 / 60° (mat - gloss).
[0234] 4.4.4 Single - coat coating composition
[0235]
Table 6
[0236] 1) Exemplary commercial products: Dynapol LH830, 60% ig (branched saturated copolyester, M w = 4000 g / mol) 2) Exemplary commercial products: Dynapol LH820, 55% ig (branched saturated copolyester, M w = 3000 g / mol) 3) Exemplary commercial products: Dynapol L205 (granules) (saturated polyester, M w =150000) 4) Exemplary commercial product: Cymel 303, 98% ig (melamine resin HMMM) 5) Exemplary commercial product: Desmodur BL3370, 70% ig (blocked aliphatic isocyanate) 6) Exemplary commercial product: Vestanat EP-B1481ND, 65%ig (isocyanate crosslinker, blocked with caprolactam) 7) Exemplary commercial product: Titandioxid 2310 8) Exemplary commercial product: Aerosil R972 9) Exemplary commercial product: Acematt 810 10) Exemplary commercial product: Shieldex C303 (calcium silicate) 11) The amounts are based on the solids content of each ingredient.
[0237] The coating compositions listed in Table 6 may further include additives and fillers commonly used in primer coating compositions.
[0238] Preferred parameters for the single coat coating composition: Solid content: 40~70% by mass Pigment to binder ratio: 1.00:0.20~1.50 Viscosity: 1000 - 10000 mPa*s Density: 1.100 - 1.400 g / cm 3 。
[0239] Preparation of the cured coating layer using the primer coating composition: Suitable substrates: Z, ZE, ZM Pretreatment: Granodine 1455 (pH value 2.0 - 2.5, coating mass < 8 mg Ti / m 2 ) Curing temperature (PMT): 200 - 260 °C Residence time: 20 - 60 seconds.
[0240] Preferred parameters of the cured primer layer: Dry film thickness: 3.00 - 30.00 μm (applied directly on the pretreatment) Solid density: 1.30 - 1.80 g / cm 3 Elastic modulus: T - 0 (Tesa tear), < T - 1 no cracking (judged by T - bend) Crosslinking (MEK - DH): < 100 DH Gloss: 20 - 90 / 60° (mat - gloss).
[0241] 5. Preparation of the multilayer coating An aluminum panel (AA6014) was coated using a [spraying device] immediately after the preparation of each of the coating compositions F1 - F3 so that the dry film thickness after curing was 60 - 73 μm. After coating, the applied film was cured at 23 °C for 60 minutes.
[0242] Thereafter, a top - coating composition was prepared by mixing the base varnish Glasurit Reihe68white, the hardener 922 - 138, and the rheology additive 352 - 216 (all supplied products of BASF Coatings GmbH) in a ratio of 4:1:1. This top - coating composition was applied using a [spraying device] so that the dry film thickness after curing was 53 μm. After coating, the applied film was cured at 60 °C for 30 minutes.
[0243] 6. Acid salt mist test results The acid salt spray mist test described in section 1.2 was carried out using the coated panels prepared in section 5. The results obtained after the end of the test, in which the panels were washed with distilled water and the rust was removed with a knife after 1 hour and 24 hours, are shown in Table 7. The difference in absolute range of about 1 mm is not meaningful since the evaluation is technically difficult.
[0244] [Table 7]
[0245] 1) Aluminum panels coated with coating composition F1 and a topcoat (not containing graphene oxide or graphene oxide containing lithium ions) 2) Aluminum panels coated with coating composition F2 and a topcoat (containing graphene oxide) 3) Aluminum panel coated with coating composition F3 of the present invention and a topcoat (containing graphene oxide with lithium ions)
[0246] As can be seen from Table 7, the coating composition of the present invention containing at least one lithium ion functionalized graphene oxide resulted in a multilayer coating (MC3) with improved corrosion protection properties compared to a multilayer coating containing only graphene oxide (MC2) or not containing any graphene oxide (MC1). Thus, by incorporating at least one lithium ion functionalized graphene oxide into a primer or primer-surfacer coating composition, the corrosion protection properties of the multilayer coating containing said primer or primer-surfacer coating layer were significantly improved.
Claims
1. a) at least one graphene oxide (GO-M) containing lithium as a monovalent metal ion; b) at least one binder B and / or at least one silane compound SC, and c) at least one solvent S1 1. A coating composition comprising:
2. 2. The coating composition of claim 1, wherein the coating composition contains the at least one graphene oxide (GO-M) containing a monovalent metal ion in a total amount of 0.1 ppm to 5 wt. %, the total amount being based on the total weight of the coating composition.
3. 3. The coating composition according to claim 1 or 2, wherein said at least one binder B is selected from the group consisting of: (i) poly(meth)acrylates, (ii) polyurethanes, (iii) linear or branched polyesters or polyamide modified polyesters, (iv) polyethers, (v) polyepoxides, (vi) phenoxy resins, (vii) copolymers of said polymers, and (vi) mixtures thereof.
4. 4. The coating composition according to claim 1 , wherein the coating composition comprises the at least one binder B in a total amount of 1 to 40% by solids weight, said total amount being based on the total amount of the coating composition.
5. The silane compound SC is represented by the general formula (I) NH 2 -R 1 -Y-R 2 -Si(R a ) 3-x (R b ) x (I) (In the formula, R 1 , R 2 are, independently of each other, an alkylene group containing 1 to 10 carbon atoms, R a is an alkoxy group containing 1 to 4 carbon atoms, R b is an alkyl group containing 1 to 4 carbon atoms or an alkoxy group containing 1 to 4 carbon atoms, Y is oxygen, sulfur or NR 3 group, R 3 is hydrogen or an alkyl group containing 1 to 4 carbon atoms, and x is 0 to 1. The coating composition of claim 1 , wherein
6. 6. The coating composition according to claim 1, comprising the at least one silane compound SC in a total amount of 2 to 20% by volume, said total amount being relative to the total volume of the coating composition.
7. 7. The coating composition according to claim 1, wherein the solvent S1 is selected from the group consisting of water, aliphatic and / or aromatic hydrocarbons, ketones, esters, or mixtures thereof.
8. 8. The coating composition according to claim 1, comprising said at least one solvent S1 in a total amount of 10 to 95% by weight, said total amount being relative to the total weight of the coating composition.
9. The following steps: (a) preparing a dispersion D of at least one graphene oxide (GO-M) containing lithium as monovalent metal ion in at least one solvent S2; (b) adding the dispersion D prepared in step (a) to a mixture containing at least one binder B and / or at least one silane compound SC and at least one solvent S1; A method for preparing the coating composition of any one of claims 1 to 8, comprising:
10. 10. The method of claim 9, wherein said dispersion D contains said at least one graphene oxide containing lithium (GO-M) in a total amount of 0.05 to 5% by weight, said total amount being based on the total weight of the dispersion.
11. The method according to claim 9 or 10, wherein said Dispersion D is added in a total amount of 0.1 to 10% by weight, said total amount being based on the total weight of the prepared coating composition.
12. The following steps: (i) applying a coating composition according to any one of claims 1 to 8 or a coating composition prepared by the method according to any one of claims 9 to 11 directly onto a substrate (S), (ii) forming a film from the coating composition applied in step (i) by curing said coating composition; and (iii) optionally applying at least one further coating composition to the coating layer formed in step (ii) and curing said coating composition. A method for forming at least one coating layer on a substrate (S), comprising:
13. A coating layer or multi-layer coating (MC) produced by the method according to claim 12.
14. 1. A method of using at least one graphene oxide (GO-M) containing at least one monovalent metal ion selected from the group consisting of lithium, potassium and mixtures thereof in a composition to improve the corrosion protection properties of the composition.
Citation Information
Patent Citations
Mineral-filled degradable polyvinyl alcohol fresh-keeping film and preparation method thereof
CN108047618A
Lithium-containing salt-graphene composite material and method for preparing the same
JP2013542903A
Electrically conductive coating containing graphene-based carbon particles
JP2016500714A
Graphene oxide, graphene-polymer composite, coating liquid containing the graphene-polymer composite, steel plate coated with the graphene-polymer composite, and production methods thereof
JP2016504262A
Graphene nanocontainer-based paint, self-healing coating layer, and its manufacturing method and application
JP2020533424A